Concentrating human urine by evaporation - Hislop, Amy (Department of Civil Engineering, 2022)
The current size of the global population was estimated to be 7.7 billion people in 2019. This is expected to increase to 9.7 billion people by the year 2030. To supply sufficient food for this growing population, the use of synthetic fertilizers has become a widely adopted agricultural practice. These fertilizers, rich in nitrogen, phosphorus and potassium (NPK) nutrients, ensure rapid and adequate food supply. However, the use of synthetic fertilizers is not sustainable. This is due to nitrogen (N) being derived from synthetic ammonia (NH3) produced via the energy intensive Haber-Bosch process. The phosphorus (P) in synthetic fertilizer is also mined from non-renewable phosphate rock. Similarly, a large population size leads to the inevitable generation of waste effluents collectively known as wastewater. Currently, wastewater is transported to and treated in traditional wastewater treatment facilities to ensure that nutrients in the wastewater are removed. This ensures that when the treatment plant effluent is released back into bodies of natural water, these bodies of water are not polluted. However, the cost associated with the treatment of wastewater and the maintenance of such facilities is high. As a result, less affluent countries have not been able to adequately maintain wastewater treatment facilities. One component of the wastewater that is treated in such facilities includes black water. This contains urine, faeces and other excreta that are flushed down the toilet. Although human urine contributes approximately 1% by volume, to the total wastewater generated, this urine contains approximately 80%, 56% and 63% of the total N, P and K found in domestic wastewater, respectively. In addition, traditionally black water is flushed down a toilet and enters the wastewater system, but a large portion of the global population do not have access to flushing toilets and clean drinking water. Furthermore, traditional flushing toilets use significant amounts of clean water, which in water scarce regions is a waste of an otherwise precious resource. These two ideas combined drives the need to rethink the current sanitation and wastewater practices. Rethinking current sanitation and traditional wastewater treatment practices encompasses a more wholistic approach towards achieving global sustainability – this approach considers resource recovery and reuse. As urine is rich in the same NPK nutrients required in synthetic fertilizers, it has been proposed to separate and collect this urine through source separating toilets, and more recently, waterless urinals. Before re-use, the urine should be treated and turned into a urine-based fertilizers or other products. The nutrients contained in the collected urine can be recycled back into the environment while simultaneously reducing the need for synthetic fertilizers. Separating urine from wastewater also lowers the N and P concentration entering the traditional wastewater treatment plants. This results in a wastewater stream that has a more favorable C:N:P nutrientratio for conventional wastewater treatment. Thislowers the volume requirement of the wastewater treatment plant, allowing for treatment with a relatively short sludge age. A shortened sludge age corresponds to a smaller requirement in plant volume, with lowered infrastructure and associated maintenance costs on the treatment plant. The use of waterless urinals not only allows for the removal of urine from wastewater, but also minimizes the clean water traditionally used when flushing urinals. From previous studies, it was shown 11 g of solid fertilizer could be harvested from 1 kg of urine collected in the urinal. The literature showed a diverse range of urine treatment and concentration options with evaporation being the most common. The experiments conducted in previous literature differed to the experiments in this thesis due to the chosen operating conditions (pH, temperature, humidity etc.) as well as the type of urine studied (fresh, hydrolyzed and stabilized). Furthermore, few studies focused on maximising the recovering of all key nutrients (N, P and K). Therefore, this study aimed to investigate these aspects through experiments and simulations. The purpose of this dissertation was to further understand the fertilizer produced from human urine. More specifically, this dissertation aimed to experimentally determine the urine stabilization technique that gave the highest N, P and K nutrient recoveries at a water removal interval of 100%. This dissertation also aimed to determine the effect of water removal on the solids formed when using the preferred urine stabilization method of calcium hydroxide dosing. From this, a comparison between experimental and theoretical results was presented. It was also desired to use theoretical simulations to determine the influence of urine composition on the preferred stabilization process and similarly, the influence of temperature on the preferred stabilization process. The final aim of this dissertation was to determine the energy consumed when evaporating water from urine stabilized through the preferred stabilization process. To further study the solid fertilizer produced from human urine, a series of experiments and simulations were conducted. Firstly, six synthetic urine solutions and three real urine solutions, each stabilized using different treatment techniques, were evaporated. The success of each stabilization treatment was assessed in terms of the measured NPK recovery in the urine solution. Once the preferred urine stabilization method was chosen from the NPK experiments, this urine stabilization method was used when evaporating urine solutions. Urine solutions were evaporated to water removals of 50%, 75% and 100% respectively. At each water removal percentage, the total mass of solids formed was measured, as well as the N, P and K concentrations in these resulting solids. Experimental results were compared to the theoretical results which were obtained from thermodynamic simulations. A further comparison was drawn by comparing the evaporation of synthetic and real Ca(OH)2 stabilized urine solutions. Ca(OH)2 stabilized synthetic urine solutions included both a solution with excess (unfiltered) Ca(OH)2 as well as a filtered synthetic urine solution. The reason an excess Ca(OH)2 stabilized synthetic urine solution was included in the comparison was to compare the influence of excess Ca(OH)2 on the pH of the urine solution. Thermodynamic simulations predicted that a urine solution with excess Ca(OH)2 was predicted to have a greater buffering capacity against CO2 compared to a filtered urine solution. A comparison was also drawn between the three urine solutions by studying the mass of remaining solution over time, as well as the scale formed in the synthetic and real urine solutions. A final experimental aspect considered urea hydrolysis in solution between temperatures of 40°C to 70°C, at a relative humidity of 40%. Urea solutions were evaporated at different temperature conditions in a climate chamber to determine the extent of urea hydrolysis . These experiments were evaporated for 95 hours. Urea hydrolysis experiments were repeated at 40°C and 70°C. However, these experiments were stopped once 100% of the water was removed from solution, shortening the evaporation time to 53 hours for the 70°C experimental run. Using a fixed urine composition, additional thermodynamic simulations were run. One set of simulations varied evaporation temperature and the second set of simulations varied stabilized urine composition by introducing four additional stabilized urine streams. From the simulated results, the total mass of solids as well as the mass of NPK solids were used to determine the influence of temperature and composition on the chosen stabilized urine solution. The results from the thermodynamic simulations were further processed using a basic mass and energy balance to develop a first estimate of the energy input associated with the evaporation process. This estimate was done independently for both varied temperature and varied composition conditions. From the experimental procedure, it was determined that Ca(OH)2 stabilized human urine was the preferred urine stabilization treatment as this urine solution had a nitrogen recovery of 109%. As P and K components of each urine solution were non-volatile, the preferred urine stabilized treatment was chosen by considering the solution with the highest N recovery. Although acetic acid and citric acid stabilized synthetic urine solutions has N recoveries of 103% and 93.5% respectively, it was decided that stabilizing with Ca(OH)2 power is a better stabilization method. This decision was made considering the precise dosing required when acidifying urine. This method would require additional equipment such as a dosing pump, compared to Ca(OH)2 stabilization which requires no dosing equipment. Urine stabilization with Ca(OH)2 required only the pre-addition of sufficient Ca(OH)2 powder to the urine solution. Using Ca(OH)2 stabilized synthetic urine, simulations were compared to experimental results at 50%, 75% and 100% water removal. It was found that the simulations did not compare well with experimental results. A total of 18.8 g of solids were predicted to form at 100% water removal. Experimentally 22 g solids were formed. Additionally, at 75% water removal a peak in N, P and K recovery was experimentally observed but this was not observed in the simulation results. Reasons for this deviation include the loss of ammonia to the atmosphere due to ammonia volatilization, which were not accounted for in thermodynamic simulations. The loss of urea due to urea hydrolysis was also not accounted for in OLI where experimentally 8.12% urea loss was observed at 70°C. When considering the influence of temperature on the solids formed in Ca(OH)2 stabilized urine, the simulations showed a decrease in solids with an increase in temperature. Furthermore, a change in urine composition showed that the mass of solids that formed depended on whether the quantity of ions that are present in major salts, increased or decreased in solution. Lastly, when using the simulation results to determine the input energy requirement associated with the process, it was seen that the overall input energy requirement increases with an increase in evaporating temperature. However, a changing urine composition did not have a significant effect on the overall energy input. When costing this energy requirement, a urine-based fertilizer could be produced via the evaporation process at a cost of 0.63 R kg-1 . When compared to available synthetic fertilizers, which are sold for between 13.17 and 24.53 R kg-1 , there appears to be a good business case for urine-based fertilizer production. Considering the information presented in this dissertation, it was recommended that future work consider investigating the rate of urea hydrolysis at further different operating temperatures and evaporation rates. Additionally, when considering Ca(OH)2 stabilized synthetic and real urine, Ca(OH)2 stabilized synthetic urine was a good proxy to Ca(OH)2 stabilized real urine. However, there were slight discrepancies, especially in terms of evaporation rates. Therefore, it is recommended that all the different stabilization methods used in this dissertation that were based on synthetic urine, be tested also with real urine. It was also recommended that the thermodynamic simulations account for urea hydrolysis, NH3 volatilization and the formation of CaCO3 during evaporation in future work. Finally, it was recommended that the solid fertilizer formed after complete water removal by evaporation be tested to determine its applicability to growing different crops, as well as to determine how this fertilizer compares to commercial and synthetic fertilizers.